Molecular pathogenesis and signal transduction by helicobacter pylori - Tegtmeyer, Nicole; Backert, Steffen (Springer, 2017)
This volume reviews the current state of research concerning bacterial virulence factors and the infection biology of Helicobacter pylori, which is the leading cause of peptic ulcers and gastric cancer worldwide. The chapters include cutting-edge findings on this fascinating microbe and discuss the general strategies of H. pylori infection and persistence, news on important H. pylori virulence factors, crosstalk with the microbiota, hot novel models and signaling mechanisms, risk factors of gastric disease and stomach cancer, and the impact of H. pylori infection on non-gastric diseases. Written by internationally respected scientists, this book will appeal to clinicians, researchers and advanced students alike.
Keywords: Helicobacter pylori infections -- Pathogenesis.; Pathology, Molecular.; elektronické knihy; electronic books